2005
DOI: 10.1073/pnas.0501202102
|View full text |Cite
|
Sign up to set email alerts
|

Control of T helper 2 cell function and allergic airway inflammation by PKCζ

Abstract: Asthma is a disease of chronic airway inflammation in which T helper (Th) 2 cells play a critical role. The molecular mechanisms controlling Th2 differentiation and function are of paramount importance in biology and immunology. PKC has been implicated in the regulation of apoptosis and NF-B, as well as in the control of T-dependent responses, although no defects were detected in naïve T cells from PKC ؊/؊ mice. Here, we report that PKC is critical for IL-4 signaling and Th2 differentiation. Thus, PKC levels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
101
1
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(113 citation statements)
references
References 25 publications
(31 reference statements)
10
101
1
1
Order By: Relevance
“…For these reasons, we sought to determine whether PKC / is necessary for an optimal Th2 inflammatory response in vivo, although it does not seem to be necessary for Th2 differentiation driven by the exogenous addition of IL-4 under standard in vitro conditions. In this regard, it is well established that Th2 cells play a critical role in the development of allergic airway inflammation (11). Because our data show that PKC / is required for a proper balance of Th2/Th1 cytokines in vitro, we reasoned that PKC / might affect the airway allergy response in vivo.…”
Section: Generation Of Conditional Pkc / Knockout Mice On Activated Tmentioning
confidence: 91%
See 3 more Smart Citations
“…For these reasons, we sought to determine whether PKC / is necessary for an optimal Th2 inflammatory response in vivo, although it does not seem to be necessary for Th2 differentiation driven by the exogenous addition of IL-4 under standard in vitro conditions. In this regard, it is well established that Th2 cells play a critical role in the development of allergic airway inflammation (11). Because our data show that PKC / is required for a proper balance of Th2/Th1 cytokines in vitro, we reasoned that PKC / might affect the airway allergy response in vivo.…”
Section: Generation Of Conditional Pkc / Knockout Mice On Activated Tmentioning
confidence: 91%
“…The number of double-positive cells (CD4 ϩ CD8 ϩ ) and single-positive cells (CD4 ϩ or CD8 ϩ ) in the thymus also did not differ in conditional PKC / -deficient and wild-type mice (Table S2). Because PKC has been shown to play a critical role during Th2 differentiation (11), and because of the high homology between the 2 aPKCs, we sought to determine whether the conditional deletion of PKC / in activated T cells would produce an effect similar to that of PKC deficiency. To do so, we stimulated purified naïve CD4 ϩ T cells from mice of different genotypes with anti-CD3 in the absence or in the presence of anti-CD28; the levels of different secreted cytokines were detected by ELISA.…”
Section: Generation Of Conditional Pkc / Knockout Mice On Activated Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, the I B-␣ increase observed in PKC Ϫ/Ϫ AM could result from de novo transcription and might be referred to a compensatory increase of PKC / . However, Western blot analysis of lung extracts from wt and PKCdeficient mice for PKC and PKC / protein expression with specific Abs revealed that the level of PKC / is not affected by the loss of PKC (55), rendering the latter explanation unlikely. The LPS-mediated I B-␣ increase in PKC Ϫ/Ϫ AM was abolished by pretreatment of the cells with SP-A, proposing that SP-A not only fails to stabilize I B-␣, but provides a signal that triggers I B-␣ degradation, presumably by activating IKK in a PKC -independent way.…”
Section: Discussionmentioning
confidence: 99%